Influence of socio-economic factors on sheep mortality and sales constraints faced by small-scale sheep producers in Nkangala District, Mpumalanga Province, South Africa - Mogashoa, Stanley Mokgatla (My University, 2015)
The study was carried out to determine influence of socio-economic factors on sheep mortality and sales constraints faced by small-scale sheep farmers of Nkangala District in Mpumalanga province. A field survey was carried out in six local municipalities of Nkangala District. Individual interviews were conducted in 132 households who owned sheep using semi-structured questionnaire. Flock size ranged from 1 – 32 sheep (mean flock size was 21.1). The estimated odds ratio shows that variables such as type of sheep housing, production methods adopted by the farmers, availability of supplementary feed and accessibility of veterinary services and extension service had high probabilities of influencing both sheep mortality and sales, whereas variables such as gender and wealth status of the farmer affected sheep sales, but not significant in affecting sheep mortality. The age of the farmer and sheep breed owned by the farmer were not significant in affecting both sheep mortality and sales. About 90 % of farmers keep sheep for income generation in order to meet family expenditures. Over 70 % of male owned large proportion of sheep across all municipalities, while females and youth were less involved in sheep production across all municipalities. Natural veld was the major source of feed for sheep flocks. In general, majority of farmers sourced their breeding stock from auction while few sourced from commercial farms. About 95 % of respondents kept indigenous sheep breeds. Particular breed of sheep was kept for various reasons which included multiple births, adaptation to environment, good temperament, and good mothering ability. Undefined breeding and lambing seasons across all municipalities was common. The majority of respondents practiced extensive production system with improper sheep housing structures and were more likely to experience feed shortage, high percentage of sheep mortality and low sheep v sales. Low income, inadequate access to veterinary and advisory services affected most of sheep producers and as a result, farmers were not able to provide supplementary feeds and medication for their animals to enhance profitability. Diseases and feed shortage contributed to sheep mortality and low sheep sales. As a result, less number and poor quality of sheep were produced. Lack of financial support and distance to market had negative effect on sales and mortality of sheep on small scale sheep producers. It was concluded that government should strengthen accessibility of veterinary and advisory services by small scale sheep producers, initiate accessible credit schemes and arrange accessible markets for these farmers to ensure sustainable sheep farming.
Thesis (M.A. Agricultural Management (Animal Production)) -- University of Limpopo, 2015
Keywords: Sheep mortality; Sheep production; Sheep -- Mortality; Sheep breeds; Sheep -- South Africa -- Mpumalanga